ORGANIZACIÓN CONTABLE A LA LAVADORA Y LUBRICADORA JELY’S CAR SERVICE DE LA CIUDAD DE CATACOCHA DURANTE EL PERIODO DE AGOSTO-OCTUBRE DEL 2017 - Saraguro Guamán, Luis Xavier (2019)
The present thesis titled "ACCOUNTING ORGANIZATION TO THE WASHING MACHINE AND LUBRICATOR JELY'S CAR SERVICE OF THE CITY OF CATACOCHA DURING THE PERIOD OF AUGUST-OCTOBER 2017", was carried out with the purpose of developing the practical application of the Accounting System that facilitates the control and recording of daily operations through compliance with each of the specific objectives that were raised and allows the owner to have sufficient financial and economic information. In order to comply with the proposed objectives and obtain the necessary information, the interview was conducted with the Owner Manager, to know the situation that the company is going through, having as reference all the invoices of purchases and sales, and thus be able to carry out the guided accounting organization under the International Accounting Standards (NIC); in order to know their economic-financial situation and obtain the Financial Statements; For this purpose, a plan and manual of accounts according to the economic activities of the washing machine and lubricator were elaborated. Through a physical verification and based on all the information collected, an Initial Inventory of all the goods, values and obligations of the Washing Machine was prepared; the respective assistants records were designed 6 detailing in these the transactions made in cash or on credit, payment roles and provisions detailing the income and expenses that each worker receives monthly, same that sustain the records of daily operations in the Daily Book , General Ledger, to later verify the balances in the Balance of Verification and the respective adjustments in the Worksheet, finally the Financial Statements were elaborated. The results show the entire accounting process obtained as of October 31, 2017, in the structure of the Statement of Financial Position a Total Asset of $ 151,438.41 was acquired, it has a Total Liability of $ 16,489.77 and a Net Worth of $ 134,948.64, The Income Statement reflects a loss of $ 7,021.19 and the Statement of Cash Flow with a final decrease of $ 3,893.06. In the application of Financial Indicators as Liquidity was reflected a Liquidity of $ 2.85, the Indebtedness indicator shows 11% of external financing and a Working Capital of $ 30,580.17, which allowed the owner to have a better vision to face short-term obligations and make sound decisions to increase your income. At the end of the thesis work, the main conclusion is reached that the Washer and Lubricator does not have real and timely information to make corrective decisions in favor of the improvement of the washing machine's activities.